Birth weight modifies the relation between adulthood levels of insulin-like growth factor-1 and type 2 diabetes: a prospective cohort study - Yoriko Heianza; Lu Qi; Tao Huang; Hao Ma; Vivian A Fonseca; Woon-Puay Koh; Mengying Wang; Tingting Geng (BMJ Open Diabetes Research & Care, 2021)
Introduction Insulin-like growth factor-1 (IGF-1) has been implicated in fetal and early-life growth and development of type 2 diabetes (T2D). We aimed to examine the interaction between circulating IGF-1 and birth weight in relation to risk of T2D.Research design and methods We included 181 090 adults, aged 39–70 years in the UK Biobank Study, who were free of diabetes or major cardiovascular diseases at baseline. Serum IGF-1 levels were determined using chemiluminescent immunoassay method. Birth weight was self-reported; a Genetic Risk Score (GRS) was calculated to define the genetically determined birth weight. The outcome was the incidence of T2D.Results We identified 3299 incident T2D cases over an average of 9.9 years of follow-up. Among the participants with birth weight of ≥2.5 kg, IGF-1 levels were inversely associated with T2D risk in a dose-dependent manner (p-trend<0.001). In contrast, the association was not significant among those with birth weight of <2.5 kg (p-interaction=0.001). The GRS of birth weight did not interact with IGF-1 levels on T2D risk.Conclusions Our results indicate that birth weight significantly modifies the relation between adulthood levels of circulating IGF-1 and the risk of T2D. Our findings highlight the importance of early-life risk factors in the development of the lifecourse prevention strategies targeting IGF-1 and T2D.